Use of Indocyanine Green Fluorescence Angiography and Prophylactic Endoscopic Stenting in Esophagectomy for Acute Esophageal Necrosis - van Liebergen, Lisanne; Kaiser, René; Sibbert, David Sebastian; Meiners, Stefan; Claussnitzer, Christian; Soelter, Jan; Schmidt, Roland; Beltzer, Christian (Zeitschrift für Gastroenterologie, 2022)
Acute esophageal necrosis (AEN) is a rare condition with high mortality. We describe a case of an AEN accompanied with multiple esophageal perforations in a 40-year-old patient. This was addressed via emergency Ivor-Lewis-esophagectomy with intraoperative Indocyanine-Green-Angiography (ICGA) and prophylactic placement of a self-expanding metal-stent (SEMS).
Keywords: akute Ösophagusnekrose; selbstexpandierender Metallstent; Indocyaningrün-Fluoreszenz-Angiographie; Ösophagusresektion; Ösophagusperforation